Detection of Galanthamine in Bulbus lycoridis radiatae by Capillary Electrophoresis with an End-column Electrochemiluminescence of Tris(2,2’-bipyridyl)ruthenium(II) - Xiang, Q.; Wang, H.; Xu, Y.; Sun, L.; Gao, Y. (Asian Journal of Chemistry, 2010)
A capillary electrophoresis with an end-column electrochemiluminescence detection method is described for the determination of galanthamine in Bulbus lycoridis radiatae without derivatization. To minimize the matrix effect and get rid of the interfering substances in crude extract of the herb, the effect of running buffer on separation and detection of galanthamine in real sample was investigated. Under the optimized conditions: electrochemiluminescence detection at 1.2 V, 15 mmol/L phosphate buffer at pH 8.49, 13 kV separation voltage, the calibration of galanthamine was linear (r = 0.998) with detection limit of 1.0 × 10-9 mol/L.